Detailled structure of the Hengill geothermal volcanic complex, Iceland inferred from 3-D tomography of high-dynamic broadband seismological data - Jousset, Philippe; Haberland, Christian; Bauer, Klaus; Arnasson, Knutur (Zenodo, 2008)
Structural features of volcanic and hydrothermal systems can be used to infer the location of magma chambers or productive geothermal areas. The Hengill volcanic triple-junction complex has a well-developed geothermal system, which is being exploited to extract hot fluids that are used for electrical power and heat production. In the framework of the I-GET project, a 4-month temporary seismological network including seven high-dynamic broadband instruments was deployed and 1D transient electromagnetic soundings (TEM) and 3D magnetotelluric (MT) surveys were performed to improve the understanding of the relationships between structural features, seismic activity and fluid production at the Hengill geothermal system. The MT and TEM data set are analysed elsewhere. The analysis of the seismological data set allowed the detection and classification of more than 600 earthquakes, among which long-period (LP) earthquakes were observed for the first time in this area. This work focuses first on a joint inversion for the 3D velocity structure and determination of the locations of the hypocentres from about 250 local volcano-tectonic earthquakes with clear P- and S-wave arrival times. The results confirm those from earlier tomography studies in this area. Integrating the seismic velocity and resistivity models in a semi-quantitative approach by cross-plotting the resistivity model with the velocity ratio V P / V S delineates a structural body with a high seismic velocity ratio and low resistivity that is interpreted as the main heat source of the geothermal system. ENGINE - FP6